Design and Development of a File Sharing System with Integrity Assurance and Audit Trail using Permissioned Blockchain and IPFS: A Case Study of DISPUSIPDA West Java - Sansan Syahrul Hidayah; Ichsan Ibrahim (SISTEMASI, 2026)
Digital transformation in government institutions requires file-sharing systems capable of ensuring document integrity, secure access control, user activity transparency, and traceable audit trails. This study designs and implements a file-sharing system based on Hyperledger Besu and InterPlanetary File System (IPFS) for document management at the Dinas Perpustakaan dan Kearsipan Daerah Jawa Barat (DISPUSIPDA). The research employed the Design Science Research Methodology (DSRM), which includes problem identification, system design, implementation, demonstration, and evaluation stages. The proposed system integrates IPFS for off-chain document storage, blockchain technology for immutable metadata recording and audit trails, and smart contracts to permanently record access rights modifications. Documents are encrypted using AES-256 before storage, while integrity verification is performed through SHA-256 hash comparison. The testing results demonstrate that all core system features operated according to the specified requirements. Document manipulation attempts were successfully detected across all testing scenarios, and the revocation mechanism effectively restricted access for users whose permissions had been revoked. Blockchain transaction latency remained within an acceptable range, while IPFS upload time increased proportionally with file size. This study contributes to the development of a file-sharing system architecture that integrates encryption, Role-Based Access Control (RBAC), revocation mechanisms, IPFS, and permissioned blockchain technology within a unified framework to support document integrity and institutional auditability in government environments.